High-mobility group protein B1 derived mutant peptide mB Box-97 inhibits the formation of neutrophil extracellular traps - More, Kunal R.; Devaraj, Aishwarya; Robledo-Avila, Frank H.; Partida-Sanchez, Santiago; Bakaletz, Lauren O.; Goodman, Steven D. (Frontiers in Immunology, 2025)
IntroductionNeutrophil Extracellular Traps (NETs) are vital for innate immunity, playing a key role in controlling pathogen and biofilm proliferation. However, excessive NETosis is implicated in autoimmunity, inflammatory and neoplastic diseases, as well as thrombosis, stroke, and post-COVID-19 complications. Managing NETosis, therefore is a significant area of ongoing research. Herein, we have identified a peptide derived from HMGB1 that we have modified via a point mutation that is referred to as mB Box-97. In our recent study in a murine lung infection model, mB Box-97 was shown to be safe and effective at disrupting biofilms without eliciting an inflammatory response typically associated with HMGB1. Here we show that the lack of an inflammatory response of mB Box-97 is in part due to the inhibition of NETosis of which we investigated the mechanism of action.MethodsmB Box-97’s anti-NETosis activity was assessed using human neutrophils with known NET inducers PMA, LPS, or Ionomycin. Additionally, mB Box-97’s binding to Protein Kinase C (PKC), in addition to downstream effects on NADPH oxidase (NOX) activation, Reactive Oxygen Species (ROS) generation and thereby NETosis were assessed.ResultsmB Box-97 significantly inhibited NETosis regardless of the type of induction pathway. Mechanistically, mB Box-97 inhibits PKC activity likely through direct binding and thereby reduced downstream activities including NOX activation, ROS production and NETosis.ConclusionsmB Box-97 is a promising dual acting therapeutic candidate for managing NET-mediated pathologies and resolving biofilm infections. Our results reveal that PKC is a viable target for NETosis inhibition independent of NET inducer and worthy of further study. These findings pave the way for a novel class of therapeutics aimed at controlling excessive NETosis, potentially offering new treatments for a range of inflammatory and immune-related diseases.